Strengthening Transport Infrastructure in Remote Areas Through A Penta Helix Collaboration Approach In West Aceh Regency - Nellis Mardhiah; Noka Omalia (Journal of Social and Policy Issues, 2025)
This study aims to analyze the application of Penta Helix collaboration approach in strengthening transportation infrastructure in remote areas in West Aceh Regency. This study is expected to provide insight for each Penta Helix actor in increasing the effectiveness of the development of collaborative transportation infrastructure and become the latest breakthrough that emphasizes socio-economic aspects to improve community welfare. The method used is a qualitative approach, through interview data collection techniques, observations and literature studies. The results of the study show that the Penta Helix elements, namely government, private sector, academia, society and media have contributed to the strengthening of transportation infrastructure. This contribution is the first step in creating a collaboration that can be an innovative solution for strengthening transportation infrastructure in remote areas. And can be an effort to overcome the challenges faced by each Penta Helix actor. This study recommends strengthening the synergy between Penta Helix elements by strengthening collaboration related to the systematic solution of problems that occur in remote areas, especially on transportation infrastructure issues, it is also necessary to develop information and coordination between Penta Helix elements and can also begin to develop ideas and concepts for the development of sustainable transportation infrastructure.